Leptin improves intestinal flora dysfunction in mice with high-fat diet-induced obesity. Issue 6 (June 2020) - Li, Xiaolin; Shi, Weihong; Xiong, Qinghua; Hu, Yungang; Qin, Xu; Wan, Guanqun; Zeng, Qi
Objective: This study investigated the effects of leptin on intestinal flora and inflammation in mice with high-fat diet (HFD)-induced obesity. Methods: Mice were fed an HFD for 8 weeks; some were concurrently administered oral leptin for 4 weeks. Pathological changes in adipose tissue were detected using hematoxylin–eosin staining; endotoxin content in adipose tissue was measured by enzyme-linked immunosorbent assay. Intestinal flora were characterized by 16S bacterial rDNA sequencing. Levels of Toll-like receptor 4 (TLR4), nuclear factor-κB inhibitor α (IκB-α), and phosphorylated c-Jun N-terminal kinase (p-JNK) were detected by western blotting. Results: Mice in the HFD group exhibited weight gain, elevated endotoxin content, and adipocyte hypertrophy, compared with the non-obese control group. Moreover, abundance of bacteria in the Bacteroides genus and community diversity were both reduced in the HFD group; reductions also were observed at corresponding phylum, class, and order levels. Levels of TLR4, IκB-α, and p-JNK were also elevated in the HFD group. Compared with the model group, leptin administration reduced the weight gain and endotoxin content, while increasing Bacteroides abundance and community diversity; it also reduced the levels of TLR4, IκB-α, and p-JNK. Conclusion: Leptin administration improved intestinal flora dysfunction and inflammation in mice with HFD-induced obesity.